Understanding the factors of mobile payment continuance intention: empirical test in an African context - Franque, Frank Bivar (2021)
Franque, F. B., Oliveira, T., & Tam, C. (2021). Understanding the factors of mobile payment continuance intention: empirical test in an African context. Heliyon, 7(8), 1-12. [e07807]. https://doi.org/10.1016/j.heliyon.2021.e07807